Dignity therapists' experience of conducting dignity therapy with terminal cancer patients in mainland China: A descriptive qualitative study. (10th August 2022) - Lin, Junyi; Zhao, Yun; Guo, Qiaohong
Abstract: Objective: This study investigated the experience of conducting dignity therapy with terminal cancer patients from the perspective of dignity therapists in mainland China. Methods: Semistructured interviews were conducted with 15 trained dignity therapists from across mainland China who have performed at least one time dignity therapy for terminal cancer patients. Data were analysed using content analysis. Results: Four main themes emerged. Firstly, therapists reported that they had many culture‐specific experiences of conducting dignity therapy with Chinese patients. Secondly, they encountered various challenges while recruiting and delivering dignity therapy to patients. Thirdly, through conducting dignity therapy, therapists gained personal development although sometimes they empathised with patients' negative emotions. Lastly, they perceived great benefits of conducting dignity therapy to the culture of caring in clinical practice and healthcare provider–patient relationship. Conclusion: Chinese culture influenced dignity therapists' experience of conducting dignity therapy in mainland China. A series of challenges and benefits of conducting dignity therapy to therapists' personal growth and clinical work were perceived. It is suggested that cultural impacts on dignity therapy implementation and the therapists' ability to deal with practical and emotional challenges need to be addressed in dignity therapy training. A more resource‐saving dignity therapy protocol would be significant for dignity therapy implementation.